(untitled) (Environment & Health, 2017)
Objective. We analyzed toxicokinetic and toxicodynamic aspects of the industrial air pollution. Materials and methods. We studied a character of the industrial emissions from stationary and mobile sources of pollution into the air basin of the city of Zaporizhzhia. We analyzed the total emissions for 1990-2013. Hygienic, analytical, mathematical-and-statistical methods, and method of causal analysis were applied. Results. More than 40 toxicants, including 6 compounds of the 1-st class and 14 substances of the 2-nd class of danger, affect the residents of the industrial city with developed metallurgical industry. Specific features of toxicokinetics and toxicodynamics of the foreground atmospheric pollutants are presented in the article. The spectrum and volume of the industrial emissions are responsible for the specificity of toxic process. Naphthalene, benzopyrene, lead, acetic and nitric acids, phenol were established to have the most ramified correlative galaxies. Threats to the health of the population are enhanced with a simultaneous environmental pollution with 13 substances with a synergism of the effect and 11 substances characterized by summing of harmful effect.